The Great East Japan Earthquake: a need to plan for post-disaster surveillance in developed countries - Jeffrey Partridge; Takeshi Kasai; Tamano Matsui; Yuzo Arima (World Health Organization Regional Office for the Western Pacific, 2011)
After a devastating earthquake and tsunami struck north-eastern Japan in March 2011, the public health system, including the infectious disease surveillance system, was severely compromised. While models for post-disaster surveillance exist, they focus predominantly on developing countries during the early recovery phase. Such models do not necessarily apply to developed countries, which differ considerably in their baseline surveillance systems. Furthermore, there is a need to consider the process by which a surveillance system recovers post-disaster. The event in Japan has highlighted a need to address these concerns surrounding post-disaster surveillance in developed countries.In May 2011, the World Health Organization convened a meeting where post-disaster surveillance was discussed by experts and public health practitioners. In this paper, we describe a post-disaster surveillance approach that was discussed at the meeting, based on what had actually occurred and what may have been, or would be, ideal. Briefly, we describe the evolution of a surveillance system as it returns to the pre-existing system, starting from an event-based approach during the emergency relief phase, a syndromic approach during the early recovery phase, an enhanced sentinel approach during the late recovery phase and a return to baseline during the development phase. Our aim is not to recommend a specific model but to encourage other developed countries to initiate their own discussions on post-disaster surveillance and develop plans according to their needs and capacities. As natural disasters will continue to occur, we hope that developing such plans during the "inter-disaster" period will help mitigate the surveillance challenges that will arise post-disaster.